Volcaniclastic Rocks in Borehole Tdp-1/84 Trobni Dol, Eastern Slovenia - Kralj, Polona (Geologija, 1998)
Uppermost 160 metres in the cored borehole Tdp-1/84 Trobni Dol, mainly consist of volcaniclastic sediments, deposited entirely in a marine environment. Two phases of volcanic activity were recognised, the second one producing huge amounts of pyroclastic material of rhyolitic composition, transported in a submarine pyroclastic flow and settled as an over 107 m thick ignimbrite deposit. After termination of explosive volcanic activity, sedimentation of fossiliferous marine mudstone Sivica continued, and immediately above the ignimbrite it contains a few cm thick layer of rhyolite-mudstone peperite. Peperite formed when magma intruded into a water-saturated muddy sediment, desintegrated into hyaloclasts owing to chill-and-quench processes, and finally, intermixed with the sediment. Overlying syn-eruptive resedimented volcaniclastics were deposited after ceassation of volcanic activity, with normal marine transport and sedimentation agents.